Oral once-daily berotralstat for the prevention of hereditary angioedema attacks: A randomized, double-blind, placebo-controlled phase 3 trial - Zuraw, Bruce; Lumry, William R; Johnston, Douglas T; Aygören-Pürsün, Emel; Banerji, Aleena; Bernstein, Jonathan A; Christiansen, Sandra C; Jacobs, Joshua S; Sitz, Karl V; Gower, Richard G; Gagnon, Remi; Wedner, H James; et al. (The Journal of allergy and clinical immunology, 2021)
BACKGROUND: Berotralstat (BCX7353) is an oral, once-daily inhibitor of plasma kallikrein in development for the prophylaxis of hereditary angioedema (HAE) attacks. OBJECTIVE: Our aim was to determine the efficacy, safety, and tolerability of berotralstat in patients with HAE over a 24-week treatment period (the phase 3 APeX-2 trial). METHODS: APeX-2 was a double-blind, parallel-group study that randomized patients at 40 sites in 11 countries 1:1:1 to receive once-daily berotralstat in a dose of 110 mg or 150 mg or placebo (Clinicaltrials.gov identifier NCT03485911). Patients aged 12 years or older with HAE due to C1 inhibitor deficiency and at least 2 investigator-confirmed HAE attacks in the first 56 days of a prospective run-in period were eligible. The primary efficacy end point was the rate of investigator-confirmed HAE attacks during the 24-week treatment period. RESULTS: A total of 121 patients were randomized; 120 of them received at least 1 dose of the study drug (n = 41, 40, and 39 in the 110-mg dose of berotralstat, 150-mg of dose berotralstat, and placebo groups, respectively). Berotralstat demonstrated a significant reduction in attack rate at both 110 mg (1.65 attacks per month; P = .024) and 150 mg (1.31 attacks per month; P < .001) relative to placebo (2.35 attacks per month). The most frequent treatment-emergent adverse events that occurred more with berotralstat than with placebo were abdominal pain, vomiting, diarrhea, and back pain. No drug-related serious treatment-emergent adverse events occurred. CONCLUSION: Both the 110-mg and 150-mg doses of berotralstat reduced HAE attack rates compared with placebo and were safe and generally well tolerated. The most favorable benefit-to-risk profile was observed at a dose of 150 mg per day.
Keywords: dvojitá slepá metoda; Double-Blind Method; Plasma Kallikrein; BCX7353; safety; plazmatický kalikrein; výsledek terapie; long-term prophylaxis; mužské pohlaví; aplikace orální; Prospective Studies; Adult; C1 inhibitor; hereditary angioedema; prophylaxis; HAE; berotralstat; Pyrazoles; ženské pohlaví; efficacy; Humans; prospektivní studie; Administration, Oral; pyrazoly; dospělí; kallikrein inhibitor; hereditární angioedémy; Female; Treatment Outcome; Angioedemas, Hereditary; lidé; Male